2020
DOI: 10.1101/2020.02.14.950097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MCT2 Overexpression Rescues Metabolic Vulnerability and Protects Retinal Ganglion Cells in Two Models of Glaucoma

Abstract: Highlights:• Loss of MCT2 in retina compromises visual function and ATP production in optic nerve • MCT2 overexpression preserves RGC soma and axon number in two glaucoma models • MCT2 overexpression improves energy homeostasis in optic nerve AbstractImproving cellular access to energy substrates is one strategy to overcome observed declines in energy production and utilization in the aged and pathologic central nervous system. Monocarboxylate transporters (MCTs), the movers of lactate, pyruvate, and ketone bo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Additionally, an increase in RGC density and an enhancement of energy homeostasis were also noted in DBA/2J mice versus the untreated cohort. This study demonstrates both the neuroprotective effect of MCT2 on glaucomatous RGCs, in addition to highlighting the potential therapeutic benefit enhanced cellular energy input may have in glaucoma treatment in the future [26].…”
Section: Mitochondrial Dysfunction Studied In Glaucomatous Retinaementioning
confidence: 69%
See 1 more Smart Citation
“…Additionally, an increase in RGC density and an enhancement of energy homeostasis were also noted in DBA/2J mice versus the untreated cohort. This study demonstrates both the neuroprotective effect of MCT2 on glaucomatous RGCs, in addition to highlighting the potential therapeutic benefit enhanced cellular energy input may have in glaucoma treatment in the future [26].…”
Section: Mitochondrial Dysfunction Studied In Glaucomatous Retinaementioning
confidence: 69%
“…Mitochondrial dysfunction in RGCs, which results in defective cellular repair process thereby enhances their susceptibility to apoptosis and subsequent glaucomatous pathogenesis [25]. Harun et al studied DBA/2J mice models and showed that monocarboylate transporters (MCT), which function as lactate and ketone transportation molecules, are under expressed in glaucomatous retinae, and result in decreased ATP production [26] Mice received an injection of MCT2 (AAV2:MCT2) in order to restore MCT2 to normal cellular levels, and it was shown that RGCs were preserved in this group of mice. Importantly, following the induction of MCT2 overexpression in DBA/2 J retinae via AAV2:MCT2 injection, mitochondrial function in the retinae of these mice improved.…”
Section: Mitochondrial Dysfunction Studied In Glaucomatous Retinaementioning
confidence: 99%
“…Altering metabolic activity in mouse models of glaucoma has had protective effects for RGCs, suggesting that provision of adequate sources of energy can sustain RGC survival (Harun-Or-Rashid et al, 2020b;Tribble et al, 2021). We have increased metabolic activity in glaucomic animals by using a ketogenic diet to increase mitochondrial activity and by using an adeno-associated virus to increase MCT-2 expression, thereby increasing metabolic substrate availability in glaucomic tissues (Harun-or-Rashid et al, 2018;Harun-Or-Rashid et al, 2020a). Additionally, restoration of nicotinamide adenine dinucleotide (NAD + ), a critical electron carrying molecule for the citric acid cycle and glycolysis, to glaucomatous retina with administration of vitamin B 3 protects RGCs (Williams et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…MCT2, a major monocarboxylic acid transporter, is involved in the transport and metabolism of lactate (Lund et al 2018 ). MCT2 plays an important role in cellular energy metabolism (Harun-Or-Rashid et al 2020 ). Recent studies have shown that neurodegenerative diseases, such as Parkinson’s disease (PD) and AD, are related to impaired energy metabolism (Kori et al 2016 ; Agnihotri and Aruoma 2020 ).…”
Section: Introductionmentioning
confidence: 99%